Intellectual capital and its impact on business performance: An empirical study of Portuguese hospitality and tourism sectors - Costa, Vânia (2020)
Purpose: The propose of this study is to determine the influence of Intellectual Capital (IC) and its components’ impact on Portuguese tourism organizations’ business performance through Return on the assets (ROA). This work evaluates and compared the intellectual capital in its four dimensions: (i) capital employed; (ii) human capital; (iii) structural capital and (iv) relational capital. Design/methodology: To approach the aim of the study the method Value Added Intellectual Coefficient (VAICTM) was applied and the practical data were collected from the Simplified Business Information (IES) through SABI (Iberian Balance Sheet Analysis System) database. The economic and financial information was collected from balance sheets and financial reports of 46.951 Portuguese companies in the hospitality and tourism sector during 2016. Multiple regression analysis was employed to identify the effect of IC components’ that significantly contribute to the company performance. Findings: The paper reveals that VAICTM, human capital efficiency coefficient (HCE), capital employed efficiency coefficient (CEE) and ROA are positively related among Portuguese’s hospitality and tourism sector. However, the structural capital efficiency coefficient (SCE) presents a negative association with profitability and the results of the relationship between the variable relational efficiency coefficient (RCE) and ROA do not present statistical significance. Practical implications: The application of the VAICTM model presented in this paper provides a basis for practical application for management. Originality/value: The paper represents a pioneering attempt to understand the relationship of intellectual capital and firm’s profitability on Portuguese hospitality and tourism sector’s, to provide solid recommendations for the importance of intellectual capital in the sustainable growth of organizations in this sector.